Удосконалення механізмів звернення громадян до органів місцевого самоврядування в Україні - ЯТЧЕНЯ Юлія (My University, 2023)
АНОТАЦІЯ Ятченя Ю. Удосконалення механізмів звернення громадян до органів місцевого самоврядування в Україні. – Рукопис. У магістерській роботі обґрунтовано теоретичні основи і розроблені практичні рекомендації щодо удосконалення механізмів звернення громадян до органів місцевого самоврядування в Україні. Досліджено сутність, цілі та види звернень до органів влади. Звернення громадян виявилися важливим засобом демонстрації суспільно-політичної активності та інтересу мешканців до громадських справ. Всі звернення громадян до органів влади виконують основні функції. Основними формами звернень громадян до органів влади є: заява, скарга, пропозиція. Досліджено закордонний досвід звернення громадян до органів влади. Наголошено, що іноземні держави надають великого значення праву на звернення, оскільки воно дозволяє громадянам брати участь у прийнятті важливих публічних рішень, захищати свої права та свободи, контролювати органи влади від зловживань. Право громадян на звернення закріплено на законодавчому рівні та поширюється на всі органи виконавчої влади та місцевого самоврядування, їх посадових осіб та інші органи, які уповноважені законом на здійснення владних управлінських функцій. Визначено, що вирішальним чинником модернізації механізмів звернень громадян в Україні до європейської спільноти є індивідуалізація діалогу, що пояснюється незавершеністю процесів політичного структурування суспільства та необхідністю відкритості та прозорості під час підготовки та прийняття державних управлінських рішень. Запропоновано з метою усунення виявлених суттєвих та технічних недоліків у нормативному регулюванні механізмі звернення громадян в Україні внести зміни до Закону України «Про звернення громадян». Ключові слова: звернення громадян, механізм реалізації права на звернення, письмове звернення, пропозиція. 3 SUMMARY Yatchenia Yu. Improvement of the mechanisms of citizens' appeal to local self-government bodies in Ukraine. - Manuscript. In the master's work, the theoretical foundations are substantiated and practical recommendations are developed for improving the mechanisms of citizens' appeals to local self-government bodies in Ukraine. The essence, goals and types of appeals to authorities were studied. Appeals of citizens turned out to be an important means of demonstrating socio-political activity and interest of residents in public affairs. All citizens' appeals to authorities perform basic functions. The main forms of citizens' appeals to authorities are: application, complaint, proposal. The foreign experience of citizens' appeals to authorities was studied. It was emphasized that foreign countries attach great importance to the right to appeal, as it allows citizens to participate in the adoption of important public decisions, protect their rights and freedoms, and control authorities against abuses. The right of citizens to appeal is fixed at the legislative level and extends to all bodies of executive power and local self-government, their officials and other bodies authorized by law to exercise power management functions. It was determined that the decisive factor in the modernization of the mechanism of citizens' appeals in Ukraine to the European community is the individualization of dialogue, which is explained by the incompleteness of the processes of political structuring of society and the need for openness and transparency during the preparation and adoption of state management decisions. It is proposed to introduce the following changes to the Law of Ukraine "On Citizen Appeals" in order to eliminate identified significant and technical deficiencies in the regulatory regulation of the citizens' petition mechanism in Ukraine. Key words: appeal of citizens, mechanism of implementation of the right to appeal, written appeal, proposal.